Climate neutral urban areas - Mario Losasso (Techne, 2025)
While decarbonisation is identified in a system of technical actions aimed at reducing CO2 emissions, the concept of climate neutrality represents an evolution of climate change coping strategies. Indeed, it considers the reduction of emissions of all greenhouse gases and tends to assume a strategic and cultural value of climate protection, with progressive involvement of the production system and the organisation of cities. Effective approaches to design involve new ways and priorities in Its conception through efficient use of resources and improved urban infrastructure, including green infrastructure, with the capability of integrating buildings into renaturalised contexts. Interpreting, managing and reprogramming innovative action in urban regeneration and architectural design requires recomposing, actualising, the relationship between communities and nature through the tools, enabling devices and mediums of culture and technology.